EXPRESSION AND PURIFICATION OF THE Chlamydomonas BLUE-COPPER PLASTOCYANIN PROTEIN - Ranatunga, Don Ruwan (My University, 2009)
Plastocyanin (PC) is a type 1 blue copper (Cu) protein found in the thylakoid lumen of plant and algal chloroplasts and in some cyanobacteria. It carries electrons from the cytochrome bf complex to the photosystem I reaction center. The ?-barrel structure of PC provides a binding site for the bound copper atom, which undergoes oxidation and reduction during electron transfer. In the oxidized state, the Cu center has a large absorbance peak centered at 597 nm, providing a convenient marker for purification and quantification of the protein. The atomic 3D structures of the Chlamydomonas reinhardtii cytochrome bf complex and PC have been solved. An abundant source of Chlamydomonas PC would be useful for detailed structure-function studies of electron transfer and interactions between these important electron transfer partners. I have expressed in Escherichia coli the Chlamydomonas PC as a His-tagged, thioredoxin fusion protein. The fusion protein, purified by metal-chelating and anion-exchange chromatography, carries a Cu atom as shown by its absorbance spectrum and has a characteristic redox midpoint potential of +375.5 + 1.5 mV at pH 7.0. However, the molar Cu content of the purified protein was only ~10%. One hypothesis for low Cu incorporation is that differences in cis-trans isomerization of proline 36 (in mature C. reinhardti PC) near the Cu pocket might hinder Cu binding. Pro36 is in the less common cis configuration in PC structures. This has been tested by site-directed mutations F35S and AGF33-35KLS that made the PC protein of the green alga Chlamydomonas more similar to that of the cyanobacterium Synechocystis sp. PCC 6803. Unfortunately, these modifications did not significantly improve Cu incorporation, nor did attempts at in vitro Cu reconstitution into the fusion protein nor the separated PC. Other possibilities for low Cu incorporation include interfering metal ion interactions during His-bind, Ni-chelating chromatography or steric constraints imposed by the thioredoxin fusion partner. Another approach for producing Chlamydomonas PC was the expression from plasmids that encode the pelB leader sequence for export of the native PC to the E. coli periplasm. Although the PC yield from these plasmids is low, this strategy might avoid problems that appear to be associated with the thioredoxin fusion protein and immobilized metal ion affinity chromatography.
A Thesis Submitted In Partial Fulfillment of the Requirements For the Degree of Master of Science-Biology Microbiology
Keywords: Electron transport; Copper proteins; Chlamydomonas; Plastocyanin